The importance of the assembling of DNA strands on the performance of electrochemical genosensors - Batistuti, Marina R. (2020)
Electrochemical biosensors have been extensively studied due to their capacity for rapid and accurate detection of a wide variety of target molecules or biomarkers. Impedimetric DNA hybridization sensors are based on tracking negative charge variation over the electrode surface owing to the target sequence of hybridization to the single-stranded immobilized DNA probes. However, the development of this platform requires an understanding of how to control the immobilization and the structure formed on the interface. The DNA assembling, as is the case of the immobilization of the single-stranded DNA on the electrode surface and the subsequent hybridization, is crucial for the performance of the biosensor and is dependent on the solution environment characteristics, as we evidenced here. Particularly, the influence of DNA probe preparation and immobilization on gold surfaces were investigated using different protocols. The influence of negatively charged redox couple in solution was studied by impedance spectroscopy and we succeed in obtaining stable and reproducible results using target sequences from 10 pmol L−1 to 1 mmol L−1. We also verified that the ionic strength of the buffer has a strong influence over the immobilization process and sensor performance.